Understanding the lasallian partners’ perceptions towards the lasallian spirituality in La Salle Gakuen-Kagoshima - Mariano, Enrico Anthony I. (Animo Repository, 2021)
After 70 years, La Salle Gakuen Kagoshima is in need of an honest evaluation of the understanding and appreciation of their Christian Identity through the Lasallian Spirituality. This study is the first critical step for such efforts of evaluation to happen since there had been no recorded data relative to the profile of these Japanese Lasallian partners and how they live out the three dimensions of the Lasallian Spirituality: the Spirit of Faith, Zeal for Service and Communion in Mission. With the Congregation for Catholic Education inviting all members of Catholic schools to strive “to become a Christian community…” (Educating, Together, CCE #32), there is a need to first know then understand the perceptions and realities of the Lasallian partners in La Salle Gakuen Kagoshima towards their Lasallian identity especially since these perceptions and realities are influenced by the peculiarity of the Japanese work culture. The study used the Lasallian Attitudinal Scale for Lasallian Association developed by Langthaler with 35 respondents from the Administration, Faculty, Support Staff and Dormitory Staff of La Salle Gakuen Kagoshima. The results of the data suggest a complementarity with the analysis on the Lasallian Spirituality (Faith, Service and Communion), the Catholic Education and the Work-Work Theory. Furthermore, the results lead to an important challenge to reflect on what steps can be done for the Japanese Lasallian partners to help them recognize their important responsibility as members of a Catholic institution to work towards the renewing of their secular and religious participation towards the educational mission of the church and the Institute of the Brothers of the Christian Schools.